'Favoritism is the secret of efficiency!' Admiral Sir John Fisher as the First Sea Lord, 1904–1910. Issue 3 (2nd July 2016) - Tikkanen, Henrikki
Abstract: Favoritism in the organizational context is often regarded as dysfunctional and detrimental to organizational performance. On the other hand, it could function as a tacit-knowledge-based mechanism for making sure that the right people are in right positions in an organization, especially under conditions of rapid and forceful change. This study focuses on the leadership of the controversial Admiral Sir John 'Jacky' Fisher (1841–1920). Fisher, as the First Sea Lord of the British Admiralty, led the Royal Navy through a significant but disputed technological and organizational turnaround during the pre-World War I (pre-WWI) naval arms race between Britain and Germany. Fisher saw that he would achieve his aims essentially by appointing his favorites and cronies to key positions throughout the naval organization. The aim in this study is to highlight the most important facets of the phenomenon from a strategic-leadership perspective.